A Herbal Concoction of Cinnamomum cassia and Artemisa annua Extracts Ameliorates Allergic Rhinitis in OVA-Induced Balb/C Mice by Inhibiting Th2 Signaling - Chuhyun Bae; Jisoo Kim; Soodong Park; Jaejung Shim; Junglyoul Lee (Applied Sciences, 2021)
Allergic rhinitis (AR) is an inflammatory airway disease (IAD) that is characterized by itching, nasal obstruction, and sneezing. AR is induced by Th-2 inflammatory responses such as those mediated by IgE and IL-4. This study aims to investigate the therapeutic effects of an herbal concoction, which is a combination of Cinnamomum cassia and Artemisa annua extracts (CIAR) against ovalbumin (OVA)-induced allergic rhinitis in a Balb/C mouse model. The effect of CIAR on the Th-2 mediated inflammatory response in the AR mouse model was studied by analyzing blood or nasal fluid samples. Experimental results revealed that OVA inhalation increased IgE, IL-4, IL-33, and TSLP levels, leading to Th2-type cytokine response. CIAR was found to significantly reduce the Th-2 response and levels of cytokines, including IL-4, IL-33, and thymic stromal lymphopoietin (TSLP). CIAR also down-regulated eosinophil (EOS) and basophil (BASO) levels in the blood. Histological analyses demonstrated decreased OVA-induced thickness of the respiratory epithelium in the CIAR-treated group. Collectively, our results suggest that the herbal concoction CIAR can effectively ameliorate the development of allergic rhinitis through the inhibition of Th-2 mediated responses.